Actinomycetes yang diisolat dari mangrove Rhizophora apiculata di perairan Tanjung Api-api, Sumatera Selatan - Tika Gustiana; Rozirwan Rozirwan; T. Zia Ulqodry (Faculty of Mathtmatics and Natural Sciences, 2021)
Actinomycetes is one type of endophytic bacteria that lives in the mangrove plant tissues. Bioactive compound which form Actinomycetes can be use as potential medicine in medic industry and pharmacy sector. This study aimed to isolate and identify the kinds of the Actinomycetes bacteria at mangrove Rhizophora apiculata from Tanjung Api-api waters, South Sumatera. This research method included measurement of environmental parameters, mangrove sampling, isolation, characterization and identification of bacteria. The result of research found two isolates of Actinomycetes in the lower roots (AB T4) and leaf (Leaf T2). The isolates code AB T4 had characteristics of moderate colony size, circular shape, entire edge, convex elevation, white colony color, had hyphae, rod-shaped cells, non motile, aerobic, gram positive, negative for oxidase, indole and gelatin, positive for catalase, citrate, urea, ornithine, aesculin, galactose, glucose and trehalose, OF oxidative and fermentative. While the isolates code Leaf T2 had characteristics of moderate colony size, irregular shape, undulate edge, raised elevation, creamy white colony color, had hyphae, gram positive, rod-shaped cells, non motile, aerobic, positive for catalase, ornithine, aesculin, celobiosa, glucose, lactose, melibiosa, sorbitol and trehalose, negative for oxidase, citrate, urea, gelatin and indole, OF oxidative and fermentative. Both isolates AB T4 and Leaf T2 were identified as Nocardia genus in lower root samples (AB T4) and Actinomadura genus in leaf samples (Leaf T2).